Proceedings of meeting of the World NCD Federation, Africa Region: Framing the noncommunicable diseases response and realizing sustainable development goals for the African region; December 12–14, 2018 - Davison Munodawafa (Medknow Publications, 2023)
As noncommunicable disease (NCD) burden continues to grow globally as well as in low‑ and middle‑income countries, there is an imperative to pursue opportunities and solutions that lead to risk mitigation, health promotion, and health system strengthening through integrated services for NCDs. The primary aim of integration is to reduce cost, improve efficiency, and achieve better health outcomes in relation to NCDs. The momentum around Sustainable Development Goals (SDG) and Universal Health Coverage (UHC) provides an opportunity to shift focus away from vertical health programs toward an integrated approach, particularly at primary healthcare level. The World Health Organization (WHO) 13th General Programme of Work (GPW13) sets out WHO’s strategic direction – strategic priorities, goals/impacts and outcomes, and strategic and organizational shifts for 2019–2023. Under the outcome 1.1, 1.2, and 1.3, of the GPW13, the WHO will efficiently and effectively increase coverage of essential health services by providing guidance and technical assistance to enable countries to strengthen their health systems and establish a strong foundation for integrated primary healthcare. This will help scale up context appropriate interventions that include prevention, early detection, treatment, and rehabilitation, with a view of achieving a 20% reduction in premature NCD death by 2023. Further, the 2011 UN Political Declaration on NCDs provides the mandate for multisectoral action and whole‑of‑government and whole‑of‑society responses. It mandates governments to work across sectors, including industries as broad as health, education, agriculture, sports, and environment; it also calls for intersectoral cooperation between UN agencies, governments, nongovernmental organizations, and the private sector. Pursuant of the above, this meeting was planned as a joint collaboration between the World NCD Federation (WNCDF), Chandigarh, India, and the WHO, Regional Office for Africa, NCD Directorate, together with the University of Botswana [Figure 1]. The specific objectives of the meeting were: (1) to discuss the latest advances and trends in detection, prevention, management, and surveillance of NCDs in Africa region within the context and framework of health system strengthening, UHC, and the SDG target on NCDs; (2) to share experiences, best practices, challenges, and bottlenecks of establishment and implementation of high‑level multisectoral coordination mechanism for NCDs within the framework of an overarching multisectoral coordination mechanism for health in Africa; (3) to discuss opportunities and challenges for scale‑up of NCD best buys within the African context and come up with recommendations on best practices; (4) to discuss how NCD prevention and control interventions can be accelerated in the region to meet the SDG of one‑third reduction in premature mortality.